Remote Detection of Human Vital Sign With Stepped-Frequency Continuous Wave Radar - Liu, Lanbo; Liu, Sixin (IEEE journal of selected topics in applied earth observations and remote sensing, 2014)
The stepped-frequency continuous wave (SFCW) radar technique was used to detect cardio-respiratory signals as the vital sign from a human subject positioned behind obstacles under laboratory conditions. The experiments were organized with a number of detection scenarios by collecting data from a group of human subjects. The experiments also investigated the effect of varying thickness of the obstacles, human subject postures, status of breathing, position of radar antenna relative to human subject's chest, as well as the length of survey times. The experimental results have shown that respiration as the primary vital sign can be detected with very high confidence and should be highlighted in developing radar systems for search and rescue for earthquake disaster survivors. Among the four human subject postures of face up, face down, face left, and face right, detection of the cardiologic signals can solely be achieved possibly when the subject was facing up. When the radar antennas to be placed at certain offset, not directly above the human subject's chest, it is still possible for good detection of the breathing signal. The minimum recording time for extracting respiration signal can be as short as 5 s. Even be conservative, a period of 30 s should be long enough for catching the respiratory signal with high signal to noise ratio.